2018
DOI: 10.1093/cercor/bhy310
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Ventromedial Prefrontal Cortex and Anterior Cingulate in Subjective Valuation of Prospective Effort

Abstract: The perceived effort level of an action shapes everyday decisions. Despite the importance of these perceptions for decision-making, the behavioral and neural representations of the subjective cost of effort are not well understood. While a number of studies have implicated anterior cingulate cortex (ACC) in decisions about effort/reward trade-offs, none have experimentally isolated effort valuation from reward and choice difficulty, a function that is commonly ascribed to this region. We used functional magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 65 publications
8
48
0
Order By: Relevance
“…Our conclusions align closely with a recent physical effort study, which found that the vmPFC encoded SV while the ACC tracked decision difficulty (Hogan et al, 2018). Interestingly, despite coming to the same conclusions as our own study, this study used methods more like those used in the prior cognitive effort studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our conclusions align closely with a recent physical effort study, which found that the vmPFC encoded SV while the ACC tracked decision difficulty (Hogan et al, 2018). Interestingly, despite coming to the same conclusions as our own study, this study used methods more like those used in the prior cognitive effort studies.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies have implicated a core valuation network that encodes SV across multiple domains (e.g., risk and delay), with primary foci in the ventromedial prefrontal cortex (vmPFC) and ventral striatum (VS; Levy and Glimcher, 2012; Bartra et al, 2013). Although this network was recently implicated in physical effort-based SV encoding (Hogan et al, 2018;Aridan et al, 2019), it has not been demonstrated to encode SV for choices about cognitive effort.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, choice prospects only involved varying amounts of physical effort (i.e., no prospective rewards were involved), which allowed us to examine how fundamental processes related to effort valuation were influenced by fatigue-induced changes in bodily state, separate from effects associated with reward valuation or effort/reward trade-offs. We have previously used this choice set to extract computational parameters that capture an individual's subjective valuation of physical effort in a state of rest 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Essentially, when individuals are faced with the option of exerting a certain amount of effort, versus a risky option involving either a greater amount of effort or no effort at all, they are less willing to choose the risky option while in a fatigued state. This hypothesis has its basis in previous studies of effort-based decision-making that found individuals exhibit increased sensitivity to changes in subjective effort as objective effort levels increase (i.e., risk aversion for effort) 6,7,9 . Neurally we hypothesize that decisions about prospective effort exertion have their basis in a value signal encoded in the ACC and insula.…”
mentioning
confidence: 87%
See 1 more Smart Citation